EVALUASI PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUM DESA) DI KABUPATEN MALUKU BARAT DAYA - Litualy, Janet W.; Leiwakabessy, Theophilia F.F.; Leunupun, Engrith G. (Komunitas Manajemen Kompetitif, 2025)
This study aims to evaluate how the management of financial reports of Village-Owned Enterprises (BUM Desa) in Southwest Maluku Regency. This study is a type of qualitative research using a descriptive approach. This study was conducted on 4 Village-Owned Enterprises in Southwest Maluku Regency by focusing on active Village-Owned Enterprises and those that have accountability reports and 4 selected BUM Desa, namely BUM Desa Laiwiaru, Ralmida, Ina Day and Leurana, by also collecting data on all Village-Owned Enterprises through the Village Community Empowerment, Population Control and Family Planning Service (DPMDPPKB). The results of this study indicate that BUM Desa Lawiaru and BUM Desa Ralmida and 18 other BUM Desa that are active in financial management are still not in accordance with the principles of SAK EMKM, some have not even recorded and reported their finances at all. Meanwhile, for BUM Desa Ina Day and BUM Desa Leurana which have implemented BUM Desa financial management very well starting from the Planning, Implementation, Administration and Accountability Stages have been carried out and are in accordance with accounting standards.